Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Studies in language and gender, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (Social aspects of AIDS, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

Theorizing Homophobia - Adam, Barry D. (Sexualities, 1998)
A series of contemporary theories that have been used to explain homophobia are assessed. Structural, feminist, comparative, gender panic, queer, and socio-historical theories rely on the premises of a diverse set of scholarly disciplines, and in turn, generate their own objects of analysis, whether `homophobia', `heterosexism', or `heteronormativity'. While the current flourishing of gay and lesbian studies has generated important insights into the workings of homophobia, analyses have also tended to be limited and fragmentary. This paper suggests a study of homophobic projects that combines theoretical tools able to recognize experience, discourse, structure, and history.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”--being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Female masculinity - Halberstam, Jack (J.) (Duke University Press, 1998)
Dans cet ouvrage essentiel de la théorie queer, Jack Halberstam s’attaque au statut protégé de la masculinité masculine et montre que la masculinité féminine lui offre une alternative distincte depuis plus de deux siècles. Démontrant que la masculinité féminine n’est pas une mauvaise imitation de la virilité, mais une mise en scène vivante et dramatique de genres hybrides et minoritaires, Halberstam catalogue la diversité des expressions de genre chez les femmes masculines, depuis les pratiques pré-lesbiennes du XIXe siècle jusqu’aux performances contemporaines des drag kings.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; queer; régions géographiques; sciences humaines; thématiques; états-unis

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Les scénarios sexuels des jeunes adultes latino-américains de Montréal : l'impact de l'acculturation et du genre - Arroyo, Javiera (Université du Québec à Montréal, 1997)
Keywords: IREF; amériques; discipline; genre; identités LGBTQIA2+; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; sexualité; thématiques

Présentation : du fléau social au fait social. L’étude des homosexualités - Chamberland, Line (Sociologie et sociétés, 1997)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; homosexualité; identités LGBTQIA2+; militance; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1183; sexualité; soc2014; sociologie; thématiques

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

Sexualité et espace public : visibilité lesbienne dans le cinéma récent - Nadeau, Chantal (Sociologie et sociétés, 1997)
Dans cet article, l'auteure démontre que la circulation et la consommation croissante des images lesbiennes dans l'espace public participent du phénomène complexe d'une culture du visible. Tout en soulignant les inévitables compromis qui découlent d'une telle négociation de la visibilité, elle retrace le potentiel culturel qu'une telle marchandisation de la " différence " représente pour les lesbiennes. L'identité et le désir lesbiens sont donc analysés ici en tant que produits représentationnels aptes à être consommés autant par les hétérosexuel.les que par les lesbiennes. Par une analyse des diverses stratégies de négociation du désir lesbien tirées de deux films populaires tant auprès d'un public hétérosexuel que gai (Gazon maudit et When Night is Falling), la critique confronte la matérialité de l'identité lesbienne au cinéma à la valeur de l'image saphique sur le marché de l'identité.
Keywords: approches et analyses; cinéma; corps; discipline; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; ressource en ligne; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Le sexe biologique et sa relation au sexe social - Peyre, Evelyne; Wiels, Joëlle (Les Temps modernes, 1997)
Keywords: anthropologie; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; genre; identités LGBTQIA2+; lit2815; lit3220; lit3495; premier cycle; ressource en ligne; sciences humaines; sexe biologique; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Queer studies: A lesbian, gay, bisexual & transgender anthology - Beemyn, Genny; Eliason, Michele J. (New York University Press, 1996)
This book is a wide-ranging anthology which discusses the nature and diversity of queer studies, its foundations, and some of the most pressing issues in the field.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identité sexuelle; identités; identités LGBTQIA2+; philosophie politique; postmodernisme; premier cycle; queer; sciences humaines; sex3383; sexualité; sociologie; thématiques

Le Rose et le noir : les homosexuels en France depuis 1968 - Martel, Frédéric (Epreuve des faits, 1996)
"Ce livre est une chronique des homosexuels en France, hommes et femmes, depuis 1968. L’homosexualité est un fil rouge qui relie entre eux des phénomènes majeurs : libération sexuelle, féminisme, mutation des modes de vie, lutte contre le sida, pacs… Frédéric Martel évoque les figures emblématiques et les activistes, mais aussi les débats et les combats, tout ce qui a contribué à ce que les « gais » sortent de l’ombre. Plus visibles, mieux acceptés, les homosexuels sont aujourd’hui en quête de reconnaissance." -- Site de l'éditeur
Keywords: 1900-1999; LGBTQIA2+; activisme; approches et analyses; cours; discipline; discours militant; droits des femmes*; europe; france; his4860; histoire du féminisme; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; lesbianisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Queer theory/sociology - Seidman, Steven (Twentieth-century social theory, 1996)
Bringing together some of the classic sociological statements and the new sociology of homosexual desire, this book points to new synthetic approaches to queer studies. It aims to productively engage the pioneering work of queer theorists.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; sofia; thématiques

A diplomacy of the oppressed: New directions in international feminism - Ashworth, Georgina (Zed Books, 1995)
Les contributrices abordent les problèmes du mouvement international des femmes, tels que la résolution des conflits; la violence; zones de libre-échange ; l'environnement; culture et identité nationale; santé; les média; droits humains; et l'emploi, en mettant l'accent sur la situation des femmes dans toutes les régions du monde. Destiné aux étudiants en études féministes, en sciences politiques et en études du développement
Keywords: 1900-1999; anthologie; approches et analyses; conflit; coopérative internationale; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; inégalités; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Thinking gender, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Opus, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres

Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Nomadic subjects: Embodiment and sexual difference in contemporary feminist theory - Braidotti, Rosi (Columbia University Press, 1994)
Nomadic Subjects plaide pour un nouveau type de pensée philosophique, qui inclurait les idées du féminisme et abandonnerait le mode hégémonique qui est conventionnellement adopté dans la haute théorie. La prose personnelle, surprenante et vivante de Braidotti insiste sur une intégration du féminisme dans le discours dominant. Les essais explorent les problèmes qui sont au cœur des débats féministes actuels, y compris la relation de l'épistémologie occidentale à la «question de la femme», le féminisme et l'éthique biomédicale, le féminisme européen et la façon dont les féministes américaines pourraient se rapporter aux mouvements européens.
Keywords: LGBTQIA2+; cours; discipline; europe; fem1000; genre; har4600; identités LGBTQIA2+; philosophie politique; post-structuralisme; premier cycle; régions géographiques; sciences humaines; soc2014; thématiques; épistémologie

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques

Feminist epistemologies - Alcoff, Linda Martín.; Potter, Elizabeth (Thinking gender, 1993)
Il s'agit de la première collection de théoriciennes féministes influentes à se concentrer sur le cœur de l'épistémologie traditionnelle, traitant de questions telles que la nature des connaissances et l'objectivité dans une perspective de genre.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; point de vue situé; ressource en ligne; sciences humaines; thématiques; épistémologie

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Wild desires & mistaken identities: lesbianism and psychoanalysis - O'Connor, Noreen; Ryan, Joanna (Between men--between women, 1993)
This groundbreaking book provides a challenging exploration of psychoanalytic ideas about lesbians and lesbianism. Based on the authors' clinical experience as psychoanalytic psychotherapists, it offers a new and thoughtful framework that does not inevitably pathologise or universalise all lesbianism. A wide range of psychoanalytic ideas are surveyed, from Freud, Deutsch and Jung to Lacan and contemporary object-relations theorists. Questions on sexual identity, sexual desire and gender identity, of transference and countertransference, and also of institutional practices in relation to training, are all critically - and stimunlatingly - addressed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; désir lesbien; lesbianisme; premier cycle; psychanalyse; sciences humaines; sexualité; soc2014; thématiques

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Penser le genre : quels problèmes? - Delphy, Christine (Sexe et genre. De la hierarchie entre les sexes, 1991)
Keywords: 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; genre; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques

Les transgressions du sexe et du genre à la lumière des données ethnographiques - Mathieu, Nicole-Claude (Sexe et genre : de la hiérarchie entre les sexes, 1991)
Keywords: 1900-1999; 1980-1989; anthropologie; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sexe/genre; thématiques